Quality analysis of BCG vaccine for bladder cancer immunotherapy using Shewhart control charts - A. A. Savina; A. A. Voropaev; A. A. Alesina (Биопрепараты: Профилактика, диагностика, лечение)
SCIENTIFIC RELEVANCE. The complexity of standardising immunobiologicals, including bacillus Calmette–Guérin (BCG) vaccines, requires improving the approach to statistical analysis of consistency in their quality indicators. Quality analysis tools include Shewhart control charts, which can be used for real-time and retrospective identification and analysis of trends in the processes of interest.AIM. This study aimed to analyse quality indicators of a BCG vaccine for bladder cancer immunotherapy using Shewhart control charts to monitor consistency in manufacturing processes and quality testing of vaccines.MATERIALS AND METHODS. The study involved a retrospective analysis of the bacterial concentration, dispersity index, loss-on-drying, and potency data obtained during the quality control of Imuron-vac, a BCG vaccine for bladder cancer immunotherapy, in the past 5 years. As part of the statistical data analysis, the authors calculated the means, investigated the correlation between the test results provided by the manufacturer and the quality control results obtained at the testing centre (TC), and checked the distributions for normality. Individuals and moving range control charts were plotted and analysed for each quality indicator.RESULTS. The correlation coefficients (r) ranged from 0.34 to 0.70 for the data submitted by the manufacturer and the data obtained at the TC. Pearson’s goodness-of-fit test showed that the distribution of the quality control results obtained at the TC was normal, with χ² = 14.03 for the dispersity index values and χ² = 4.93 for the loss-on-drying measurements. Shewhart control charts for loss-on-drying and potency data suggested that the production process and/or the testing process deviated from the state of statistical control. Consistency monitoring of the bacterial concentration and the dispersity index showed that the state of statistical control was achieved. The authors established control limits for further real-time monitoring of the dispersity index consistency.CONCLUSIONS. Shewhart control charts are applicable to the quality control of BCG vaccines for bladder cancer immunotherapy at the TC. Continuous monitoring of consistency in quality indicators is needed to improve the standardisation of vaccine production processes and testing methods, as this standardisation will result in high product quality.